The Effectiveness of Guidance and Counselling Services through Hypnotherapy in Overcoming Student Academic Stress: A Systematic Literature Review - Chintia Alvi Arfandita; Busmayaril Busmayaril (Electronic Journal of Education, Social Economics and Technology, 2025)
Hypnotherapy can support students in managing academic stress to achieve better academic performance. Training in hypnotherapy, especially self-hypnosis, equips students with essential self-regulation skills to cope with academic pressure effectively. This study is a systematic review aimed at updating the current body of evidence and expanding the understanding of hypnotherapy's effectiveness in alleviating academic stress among university students. The review focuses on studies published between 2000 and 2021. The method involved a comprehensive search of relevant scholarly literature, particularly studies examining the application of hypnotherapy within the context of guidance and counseling services in educational settings. The findings consistently demonstrate that hypnotherapy has a positive impact in reducing levels of academic stress, enhancing relaxation, and improving students' psychological well-being. These outcomes suggest that hypnotherapy can serve as a viable and effective complementary approach in student mental health support. The review highlights the potential of integrating hypnotherapy into counseling practices in higher education as part of holistic strategies to support students' emotional and academic resilience